Mullite-cordierite conductive sagger as well as preparation method and application thereof

By introducing tin or silver source as conductive materials in mullite-cordierite sack, the problem of affecting its electrochemical performance of the slag into the positive electrode material is solved, and the effect of improving the conductivity and electrochemical performance of the positive electrode material is achieved.

CN119841653APending Publication Date: 2025-04-18GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015801.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing mullite-cordierite sack is prone to cracking, peeling and peeling during use, causing the slag to enter the positive electrode material and affect its electrochemical properties.

Method used

Introducing tin or silver sources as conductive materials in mullite-cordierite sacks will improve the conductivity of the slags, so that it acts as a conductive bridge in the positive electrode material and improves electrochemical performance.

Benefits of technology

By introducing conductive materials, the conductivity and electrochemical properties of the positive electrode material are improved, and the problem of the slag entering the positive electrode material affecting its performance is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841653A_ABST
    Figure CN119841653A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a mullite-cordierite conductive sagger and a preparation method and application thereof. The mullite-cordierite conductive sagger is prepared from the following raw materials: mullite, cordierite and a conductive material, and the conductive material is a tin source or / and a silver source. Conductive metal elements are introduced into the mullite-cordierite sagger by utilizing the tin source or / and the silver source, so that the conductivity of the sagger slag entering positive electrode material particles can be improved, the sagger slag remaining in the positive electrode material can serve as a conductive bridge, and the electrochemical performance of the sagger burning-bearing positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a mullite-cordierite conductive sagger and a preparation method and application thereof. Background Art

[0002] At present, the sintering process of most lithium battery positive electrode materials is carried out in a roller kiln by a high-temperature solid phase synthesis method, and the sagger, as a sintering tool for roller kiln sintering, is generally made of cordierite and mullite as the main raw materials. Among them, cordierite has a low expansion coefficient, and mullite has a low expansion coefficient and high mechanical strength. Therefore, the cordierite-mullite composite material exhibits a low thermal expansion coefficient and excellent thermal shock resistance. It also has the advantages of cheap raw material price, low sintering temperature, simple preparation process, and can be recycled many times.

[0003] However, during the use of saggers, due to factors such as thermal shock and erosion penetration, cracking, peeling and flaking often occur, causing a large amount of sagger slag to enter the positive electrode material, and enter the grinder together with the positive electrode material to become micro powder. In addition, the particle size distribution of the sagger slag is close to that of the positive electrode material, so that it can pass through the screen smoothly and enter the sintered positive electrode material. However, the current existing mullite-cordierite saggers often only focus on the mechanical strength, corrosion resistance, thermal conductivity and air permeability of the sagger, and do not pay attention to its impact on the electrochemical properties of the positive electrode material. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing mullite-cordierite sagger easily leads to reduced electrochemical performance of the positive electrode material, thereby providing a mullite-cordierite conductive sagger and its preparation method and application for solving the above problem.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a mullite-cordierite conductive sagger, the raw materials of which include: mullite, cordierite, and a conductive material, wherein the conductive material is a tin source and / or a silver source.

[0007] Preferably, the mass ratio of the mullite, cordierite and conductive material is (25-35):(25-35):(30-50), preferably 30:30:40.

[0008] Preferably, the tin source is tin powder and / or tin oxide powder;

[0009] And / or, the silver source is silver powder and / or silver oxide powder.

[0010] Preferably, the particle size of the mullite is 0.05-0.5 mm;

[0011] And / or, the particle size of the cordierite is 0.05-0.5 mm;

[0012] And / or, the particle size of the conductive material is 0.05-0.5 mm.

[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned mullite-cordierite conductive sagger, comprising: mixing mullite, cordierite and a conductive material to obtain a mixture; pressing the mixture into a blank to obtain an original blank; and sintering the original blank in an oxygen-containing atmosphere to obtain a mullite-cordierite conductive sagger.

[0014] Preferably, the oxygen-containing atmosphere is air and / or oxygen.

[0015] Preferably, the pressing pressure is 1-100 MPa, preferably 100 MPa.

[0016] Preferably, the sintering temperature is 1000-1200°C;

[0017] And / or, the sintering treatment duration is 20-30 hours.

[0018] Preferably, the sintering process is followed by natural cooling in the furnace.

[0019] In a third aspect, the present invention also provides the use of the above-mentioned mullite-cordierite conductive sagger or the mullite-cordierite conductive sagger prepared by the preparation method of the above-mentioned mullite-cordierite conductive sagger in the sintering of lithium battery positive electrode materials. Preferably, the lithium battery positive electrode material is a nickel-cobalt-manganese ternary positive electrode material.

[0020] The technical solution of the present invention has the following advantages:

[0021] A mullite-cordierite conductive sagger, the raw materials include: mullite, cordierite, conductive material, the conductive material is a tin source and / or a silver source. The inventor found that during the use of the existing mullite-cordierite sagger, the sagger slag enters the positive electrode material, thereby affecting the electrochemical performance of the positive electrode material. The research found that the reason for this problem is that cordierite (Mg2Al4Si5O 18) belongs to magnesium aluminum silicate, which is non-conductive or weakly conductive. Mullite (SiO2-Al2O3) belongs to aluminum silicate, which is also non-conductive. If the micro-powder sagger slag is filled between the positive electrode material particles, it will isolate the electronic conduction of the positive electrode material, thereby greatly reducing the electrochemical performance of the positive electrode material. Based on the above discovery, the present invention uses a tin source and / or a silver source to introduce conductive metal elements into the mullite-cordierite sagger. Although it cannot change the corrosion resistance of the sagger (after ten uses, the saggers are peeling), it can improve the conductivity of the sagger slag entering the positive electrode material, so that the sagger slag remaining in the positive electrode material can act as a conductive bridge, thereby improving the electrochemical performance of the positive electrode material fired in the sagger. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is a scanning electron microscope morphology image of the material obtained from the sagger prepared in Example 1 of the present invention after being crushed during the 10th load-bearing sintering;

[0024] Figure 2 This is a physical picture of the bottom of the sagger prepared in Example 1 of the present invention corroded and peeled after 10 repeated sintering;

[0025] Figure 3 This is a physical picture of the sagger prepared in Comparative Example 1 of the present invention, in which the bottom of the sagger is corroded and peeled after 10 repeated sinterings;

[0026] Figure 4 It is a first discharge curve diagram of the positive electrode material obtained when the saggers prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 were subjected to the 10th load sintering. DETAILED DESCRIPTION

[0027] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0029] Example 1

[0030] This embodiment provides a method for preparing a mullite-cordierite conductive sagger, and the specific steps are as follows:

[0031] 1) 30 parts by weight of mullite, 30 parts by weight of cordierite, and 40 parts by weight of tin powder are mixed to obtain a mixture; wherein the particle size of the mullite is 0.1 mm, the particle size of the cordierite is 0.1 mm, and the particle size of the tin powder is 0.05 mm;

[0032] 2) placing the mixture obtained in step 1) in a mold, and pressing it into a blank at 100 MPa to obtain a sagger blank;

[0033] 3) placing the sagger blank in step 2) in a sintering furnace, sintering at 1100° C. in an air atmosphere for 25 hours, and finally cooling naturally in the furnace to obtain a mullite-cordierite conductive sagger.

[0034] Example 2

[0035] This embodiment provides a method for preparing a mullite-cordierite conductive sagger, and the specific steps are as follows:

[0036] 1) 30 parts by weight of mullite, 30 parts by weight of cordierite, and 40 parts by weight of tin oxide powder are mixed to obtain a mixture; wherein the particle size of the mullite is 0.1 mm, the particle size of the cordierite is 0.1 mm, and the particle size of the tin oxide powder is 0.08 mm;

[0037] 2) placing the mixture obtained in step 1) in a mold, and pressing it into a blank at 100 MPa to obtain a sagger blank;

[0038] 3) placing the sagger blank in step 2) in a sintering furnace, sintering at 1000° C. in an air atmosphere for 30 hours, and finally cooling naturally in the furnace to obtain a mullite-cordierite conductive sagger.

[0039] Example 3

[0040] This embodiment provides a method for preparing a mullite-cordierite conductive sagger, and the specific steps are as follows:

[0041] 1) 30 parts by weight of mullite, 30 parts by weight of cordierite, and 40 parts by weight of silver powder are mixed to obtain a mixture; wherein the particle size of the mullite is 0.1 mm, the particle size of the cordierite is 0.1 mm, and the particle size of the silver powder is 0.07 mm;

[0042] 2) placing the mixture obtained in step 1) in a mold, and pressing it into a blank at 100 MPa to obtain a sagger blank;

[0043] 3) placing the sagger blank in step 2) in a sintering furnace, sintering at 1200° C. in an air atmosphere for 20 hours, and finally cooling naturally in the furnace to obtain a mullite-cordierite conductive sagger.

[0044] Comparative Example 1

[0045] This comparative example provides a method for preparing a mullite-cordierite sagger, and the specific steps are as follows:

[0046] 1) 50 parts by weight of mullite and 50 parts by weight of cordierite are mixed to obtain a mixture; wherein the particle size of the mullite is 0.1 mm, and the particle size of the cordierite is 0.1 mm;

[0047] 2) placing the mixture obtained in step 1) in a mold, and pressing it into a blank at 100 MPa to obtain a sagger blank;

[0048] 3) placing the sagger blank in step 2) in a sintering furnace, sintering at 1100° C. in an air atmosphere for 25 hours, and finally cooling naturally in the furnace to obtain a mullite-cordierite sagger.

[0049] Comparative Example 2

[0050] The difference between this comparative example and Example 1 is that the tin powder is replaced by copper powder, and other conditions are the same as Example 1.

[0051] Test Example 1

[0052] The conductivity test was performed on the powders of the saggers prepared in the above embodiments and comparative examples, and the positive electrode material loading sintering treatment was repeated 10 times using the saggers prepared in the above embodiments and comparative examples, and the rate performance and cycle stability of the positive electrode material obtained during the 10th loading sintering treatment were evaluated. The test results are shown in Table 1 below. The steps of the positive electrode material loading sintering treatment are: weigh 10 mol of LiOH and 10 mol of Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 ternary precursor was mixed evenly, and then carried in a sagger and placed in an oxygen atmosphere, and sintered at 700°C for 10 hours. The positive electrode material was taken out of the sagger. The scanning electron microscope morphology of the sagger slag in the positive electrode material obtained by the sagger prepared in Example 1 after the 10th sintering is as follows: Figure 1 As shown in FIG. 1 (the black background is conductive glue, the irregular flakes are sagger slag, and the regular spherical objects are positive electrode materials), the sagger prepared in Example 1 has a corroded bottom after 10 repeated sinterings. Figure 2 As shown in the figure, the bottom of the sagger prepared in comparative example 1 is corroded and peeled after 10 repeated sintering. Figure 3 As shown, the first discharge curve of the positive electrode material obtained by the saggers prepared in Examples 1-3 and Comparative Examples 1-2 during the 10th load sintering is as follows: Figure 4 shown.

[0053] The test method of conductivity is as follows: the saggers prepared in the above-mentioned embodiment and the comparative example are crushed and ground through a 325-mesh sieve, about 1.00 g of the sample is weighed with weighing paper, and the sample is placed in the sample holder of the FT-7200A automatic four-probe powder resistivity tester. The powder resistance of the material is tested under a pressure of 10 MPa (three groups of parallel experiments, and the average value is taken).

[0054] The steps for testing the rate performance and cycle stability of the positive electrode material obtained during the 10th load sintering treatment are as follows: the positive electrode material obtained during the 10th load sintering treatment is used as the positive electrode material of a button cell (model: CR2032), and the button cell is assembled in the order of the negative electrode shell, gasket, gasket, negative electrode material (lithium sheet), separator (PP / PE composite film), positive electrode material and positive electrode shell, and placed in the blue electric test system for electrical performance testing; the electrical performance test parameters are set as follows: first charge to 4.4V at a rate of 0.1C, and then discharge to 2.5V at a rate of 0.1C, which is a cycle process. Then charge and discharge once at 0.5C, and then charge and discharge 50 times at 1C to test the cycle retention rate. The test results are shown in Table 1.

[0055] Table 1

[0056]

[0057] According to the test results of the above embodiments and comparative examples, although the conductive saggers prepared in embodiments 1-3 peel and slag, since the saggers are doped with conductive metal elements, the generated sagger slag is crushed together with the positive electrode material and enters between the positive electrode material powder particles, so that the sagger slag remaining in the positive electrode material can act as a conductive bridge, thereby improving the conductivity and electrochemical properties of the positive electrode material.

[0058] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A mullite-cordierite conductive sagger, characterized in that: Ingredients include: Mullite, cordierite and a conductive material, wherein the conductive material is a tin source and / or a silver source.

2. The mullite-cordierite conductive sagger according to claim 1, characterized in that: The mass ratio of the mullite, cordierite and conductive material is (25-35):(25-35):(30-50), preferably 30:30:

40.

3. The mullite-cordierite conductive sagger according to claim 1 or 2, characterized in that: The tin source is tin powder and / or tin oxide powder; And / or, the silver source is silver powder and / or silver oxide powder.

4. The mullite-cordierite conductive sagger according to claim 1 or 2, characterized in that: The particle size of the mullite is 0.05-0.5 mm; And / or, the particle size of the cordierite is 0.05-0.5 mm; And / or, the particle size of the conductive material is 0.05-0.5 mm.

5. The method for preparing a mullite-cordierite conductive sagger according to any one of claims 1 to 4, characterized in that: include: Mullite, cordierite and conductive material are mixed to obtain a mixture; the mixture is pressed into a blank to obtain a green blank; and the green blank is sintered in an oxygen-containing atmosphere to obtain a mullite-cordierite conductive sagger.

6. The preparation method according to claim 5, characterized in that: The oxygen-containing atmosphere is air and / or oxygen.

7. The preparation method according to claim 5, characterized in that: The pressing pressure is 1-100 MPa, preferably 100 MPa.

8. The preparation method according to claim 5, characterized in that: The sintering temperature is 1000-1200°C; And / or, the sintering treatment duration is 20-30 hours.

9. The preparation method according to claim 5, characterized in that: After the sintering process, the furnace is naturally cooled.

10. Use of the mullite-cordierite conductive sagger prepared by the preparation method of the mullite-cordierite conductive sagger according to any one of claims 1 to 4 or the mullite-cordierite conductive sagger according to any one of claims 5 to 9 in sintering of positive electrode materials for lithium batteries.